2004
DOI: 10.1002/pen.20083
|View full text |Cite
|
Sign up to set email alerts
|

Optimal process conditions of shrinkage and warpage of thin‐wall parts

Abstract: Optimal process conditions of thin‐wall injection molding of a cellular phone cover were investigated with the consideration of interaction effects between process parameters. L27 experimental tests based on Taguchi's method were performed, and then Cyclone Scanner, PolyCAD and PolyWorks were used to measure the shrinkage and warpage of the thin‐wall injected parts to determine the optimal process conditions. Based on the results of the analysis of variables and the F‐test, interaction effects for each observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 12 publications
2
46
0
Order By: Relevance
“…Because of some physical aspect of the process, significant deviations are observed between the dimensions and shape of the cavity and those of the final parts. Those discrepancies are caused by thermal effects such as difference between the linear thermal expansion coefficients of the mould and the polymer [26], crystallization and thermal kinetics [27], flow effects inducing filler [28] and molecular orientation gradients [29,30], as well as mould deformations [31]. Practically, the deviations from the mould geometry may be described by shrinkage and warpage, shrinkage regarding dimensional differences and warpage regarding shape differences [32].…”
Section: Introductionmentioning
confidence: 99%
“…Because of some physical aspect of the process, significant deviations are observed between the dimensions and shape of the cavity and those of the final parts. Those discrepancies are caused by thermal effects such as difference between the linear thermal expansion coefficients of the mould and the polymer [26], crystallization and thermal kinetics [27], flow effects inducing filler [28] and molecular orientation gradients [29,30], as well as mould deformations [31]. Practically, the deviations from the mould geometry may be described by shrinkage and warpage, shrinkage regarding dimensional differences and warpage regarding shape differences [32].…”
Section: Introductionmentioning
confidence: 99%
“…The Taguchi method was used for the conduction of experimental tests. The results for thin-wall parts also indicated that the packing pressure was the most important process parameter that affects shrinkage and warpage [6].…”
Section: Introductionmentioning
confidence: 76%
“…From the analysis, mould and melt temperatures, along with holding pressure and holding time, are the most significant influences on the shrinkage behaviours of three materials, although the importance of each is different for each plastic. Similar to previous study, [16] used C-Mold to explore the effect of four processing parameters and some interaction effects on shrinkage and warpage. It was found that the shrinkage in the -and -directions under the optimal process conditions with the consideration of interaction effects was smaller than those injected under the optimal process conditions without considering the interaction effects in both prediction and verification experiments.…”
Section: Isrn Industrial Engineeringmentioning
confidence: 99%
“…Another study with similar aim, which was conducted by [15], also indicated that the optimal combination of processing parameters managed to reduce the warpage of the initial thin shell plastic model significantly by 51%. In another study, [16] investigated the influence of processing parameters on shrinkage and warpage of a cellular phone casing. It was found that packing pressure is the most important parameter compared to other studied factors such as mould temperature, melt temperature, and injection speed.…”
Section: Optimization Of Injection Moulding Processing Parametersmentioning
confidence: 99%